IMPLEMENTASI PENDIDIKAN KEBENCANAAN BERBASIS KEPRAMUKAAN: PENGUATAN KECAKAPAN SIAGA BENCANA UNTUK MENINGKATKAN RESILIENSI SEKOLAH - Putri Sabrina, Luthfiah; Irnawati (Universitas Negeri Surabaya (Unesa), 2026)
Indonesia, known as the world's “disaster laboratory,” requires educational institutions to transform from mere centers of knowledge transmission into units with independent disaster preparedness capabilities. This study aims to analyze the strategic role of the Scout Movement in strengthening school resilience through the integration of applicable and contextual disaster literacy. The research method used is a Systematic Literature Review (SLR) of scientific publications and policy documents from 2016 to 2026 that discuss disaster education, scouting, and school resilience. The results of the study show a competency gap between the great potential of the Scout Movement, particularly through the Special Proficiency Requirements (SKK) curriculum, and its implementation in the field, which is still dominated by ceremonial activities and is not yet based on local disaster risks. The low level of understanding of Scout leaders regarding standard operating procedures (SOPs) for disasters and the limited availability of practical simulation facilities are the main factors hindering the strengthening of students' psychomotor skills. As a synthesis, this study formulates a collaborative resilience model that integrates school managerial policies with Scouting tactical skills. The synchronization between the Disaster Safe School program and Scouting activities is considered capable of building a sustainable, applicable, and adaptive disaster mitigation ecosystem against future disaster threats.